Lupus erythematosus, thyroiditis, alopecia areata and vitiligo - A multiple autoimmune syndrome type 3 case presentation - Alin Laurentiu Tatu; Lawrence Chukwudi Nwabudike (Our Dermatology Online, 2017)
The combination of at least three autoimmune diseases in the same patient has defined as multiple autoimmune syndrome (MAS). Abnormalities of T cell-mediated immunity and humoral immunity have been described previously in the literature. Aims of work were to investigate the 22 years old patient with lupus erythematosus for three years and autoimune thyroiditis for one year, regardind other possible autoimmune conditions and to establish a treatment to control the diseases. The clinical exam revealed some circular hairless patches on the beard appeared about three months ago and white depigmented disseminated areas started one month ago and the laboratory investigations were performed. The modified laboratory findings were total IgE 530 UI/mL, Anti-SSA (anti-RO) antibodies> 200 IU/mL, SSB negative, Antinuclear antibodies (ANA) positive and fine speckled, Lupus anticoagulant testing positive, Anti-thyroid peroxidase antibodies 951 UI/ml, TSH 4,7 µUI/mL. The diagnosis of multiple autoimmune syndrome(MAS) type 3 including Lupus erythematosus, autoimune Thyroiditis, Alopecia Areata and Vitiligo was established. Endocrine autoimmunities are associated with autoantibodies that react to specific antigens, whereas patients with collagen diseases synthesize immunoglobulins that recognize nonorgan-specific cellular targets, such as nucleoproteins and nucleic acids. Cellular autoimmunity is important in the pathogenesis MAS. The existence of one autoimmune disorder helps lead to the discovery of other autoimmune conditions.